Sons do tempo: a música na formação infomemorial e identitária do artista plástico Hermano José - Silva, Ronieli Victor da (2022)
In the scope of personal collections, the treatments aimed at the organization, access and use of the information that permeate this type of file are complex, especially when it comes to a closed collection, as is the case on screen, by Hermano José. Our study proposes, through its writing, to take the artist’s phonographic collection as a source of primary information, exploring the infomemorial characteristic of sound documents in the identity construction of its holder. It should be noted that this research aimed to understand the role of music in the infomemorial and identity formation of the plastic artist Hermano José, as well as knowing his sound preferences, through the mapping of vinyl records, generating as a product a list of titles belonging to the bequest, featuring the predominant musical genres and addressing the specifics of the phonographic collection. For the accomplishment of this study, the evidentiary method was adopted, allowing the investigative collection of fragments that answered the guiding question of this work. In this sense, we undertake an immersion among books, magazines, newspapers, manuscripts, interviews and statements in videos and audios, correlating the artist’s personal collection, thus weaving a kind of investigative search from the collection of various fragments, clues and traces. The work, in addition to presenting the musical predilection of the artist, brings a musical investigative map approaching elements and characters considered fundamental to understand the role of music, as well as its contribution in the process of infomemorial and identity formation of the plastic artist Hermano José.